The Role of English for Public Administration (EPA) in Enhancing the Employability of STIA Tabalong Graduates: A Systematic Literature Review - Muhammad Taupik; Ahmad Farhani (International Journal of Multilingual Education and Applied Linguistics, 2025)
This systematic literature review (SLR) thoroughly investigates the significant role of English for Public Administration (EPA) in improving the overall employability of STIA Tabalong graduates in an increasingly competitive job market. Employing a rigorous and structured search protocol across major academic databases such as Scopus and Google Scholar, this study carefully synthesizes key findings from relevant scholarly articles published between 2015 and 2025. The comprehensive review reveals that proficiency in EPA is absolutely crucial for effective professional communication in various public sector roles, significantly impacting a graduate's ability to secure employment and advance their career. Key findings indicate a strong correlation between specialized English skills and job opportunities, while also highlighting common challenges in EPA implementation, such as a lack of relevant teaching materials and pedagogical limitations. The findings provide concrete implications for STIA Tabalong, suggesting necessary curriculum enhancements to better align with industry demands and to bridge the existing skills gap.